2019
DOI: 10.1111/hepr.13332
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis markers as assessed by ultrasound elastography and serum samples: A large comparative study in hepatitis virus B and C liver diseases

Abstract: Aim We aimed to compare the well‐established liver fibrosis (LF) markers in Japanese patients with chronic hepatitis B (CHB, n = 331) and chronic hepatitis C (CHC, n = 886) and to discuss possible causes of differences in results between CHB patients and CHC patients. Methods Virtual touch quantification (VTQ) in acoustic radiation force impulse, Fibrosis‐4 (Fib‐4) index, aspartate aminotransferase to platelet ratio index (APRI), and hyaluronic acid (HA) were compared between the two cohorts. As an additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(128 reference statements)
1
6
0
Order By: Relevance
“…Nevertheless, it has been documented that there are differences in SWV values between CHB patients and CHC patients that have the same fibrosis stage. 32 Due to excluding patients with CHC infection, the association between SWV values and fibrosis stages demonstrated in our study is reliable and specific to CHB. In addition, since most of our participants (85%) received antiviral treatment, our findings also shed light on the use of ARFI-pSWE in evaluating fibrosis stages in CHB patients receiving antiviral therapies.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Nevertheless, it has been documented that there are differences in SWV values between CHB patients and CHC patients that have the same fibrosis stage. 32 Due to excluding patients with CHC infection, the association between SWV values and fibrosis stages demonstrated in our study is reliable and specific to CHB. In addition, since most of our participants (85%) received antiviral treatment, our findings also shed light on the use of ARFI-pSWE in evaluating fibrosis stages in CHB patients receiving antiviral therapies.…”
Section: Discussionsupporting
confidence: 49%
“… 16 Indeed, it has been documented that, in the same fibrosis stage, CHB patients had a mean SWV value significantly lower than that of CHC patients. 32 Besides, the dissimilarity in SWV cut-off values may be attributable to the references in the reference methods used to distinguish liver fibrosis stages. Our study used FibroScan, while Friedrich-Rust et al utilized liver biopsy to diagnose liver fibrosis and Ye et al relied on a combination of upper endoscopy and liver biopsy to diagnose cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified that M2BPGi can serve as a serum fibrosis marker in patients with CHB ( 30-33 ), although M2BPGi levels vary for the same fibrosis stage between patients with CHB and CHC ( 31 ). This may be partly explained by the fact that the generative nodule size and fibrous septum thickness (composed of collagen fibrils) substantially differ between patients with CHB and CHC ( 34 ). These findings support the potential role of M2BPGi as a surrogate biomarker that reflects hepatic stellate cell function ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the clinical usefulness of ultrasound elastography is not limited to the diagnosis for the degree of liver fibrosis, it can also be helpful for the prediction of development of hepatocellular carcinoma, 11,12 the diagnosis for esophageal varices, 13–16 the differential diagnosis for liver tumors, 17,18 and the prediction for postoperative complications 19–21 . However, the diagnosis for liver fibrosis using SWE can be affected by hepatic inflammation, extrahepatic cholestasis, heart failure, and underlying liver diseases themselves 22–28 . Thus, transient elastography (TE) and virtual touch quantification (VTQ) could overestimate liver fibrosis grade in patients with higher aminotransferase levels 23 .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] However, the diagnosis for liver fibrosis using SWE can be affected by hepatic inflammation, extrahepatic cholestasis, heart failure, and underlying liver diseases themselves. [22][23][24][25][26][27][28] Thus, transient elastography (TE) and virtual touch quantification (VTQ) could overestimate liver fibrosis grade in patients with higher aminotransferase levels. 23 Moreover, TE and VTQ elastography were shown to be influenced by aminotransferase levels in a multicenter retrospective study with 1242 chronic hepatitis patients.…”
Section: Introductionmentioning
confidence: 99%